The Language of History: Sanskrit Narratives of Indo-Muslim Rule - João Pedro Oliveira (Práticas da História)
Review of Audrey Truschke. The Language of History: Sanskrit Narratives of Indo-Muslim Rule. New York: Columbia University Press, 2021, 351 pp.